1973
DOI: 10.1128/iai.7.2.313-314.1973
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Chemiluminescence During Phagocytosis of Opsonized Bacteria

Abstract: A simple technique is presented for rapid screening of leukocytes of patients suspected of having a defective intracellular mechanism for the bactericidal and digestive disposal of bacteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
23
0

Year Published

1978
1978
1994
1994

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(25 citation statements)
references
References 4 publications
2
23
0
Order By: Relevance
“…Not only lysosomal enzymes, but also oxidative processes involving oxygen free radicals (OFR) have been reported as antimicrobial agents of phagocytes (2,14,20). The capacity of phagocytes to generate OFR can be studied by luminol-dependent chemiluminescence (CL) technique which is triggered, for example, by the interaction of granulocytes with particles (1,15,17,19,23). Therefore, in the present study the production of anti-porin antibodies as well as the changes in OFR generation capacity of peritoneal macrophages and lymphocyte blast transformation after injection with porins were studied to clarify the mechanism by which porin vaccine provides protection against salmonellosis.…”
Section: Immunizationmentioning
confidence: 99%
“…Not only lysosomal enzymes, but also oxidative processes involving oxygen free radicals (OFR) have been reported as antimicrobial agents of phagocytes (2,14,20). The capacity of phagocytes to generate OFR can be studied by luminol-dependent chemiluminescence (CL) technique which is triggered, for example, by the interaction of granulocytes with particles (1,15,17,19,23). Therefore, in the present study the production of anti-porin antibodies as well as the changes in OFR generation capacity of peritoneal macrophages and lymphocyte blast transformation after injection with porins were studied to clarify the mechanism by which porin vaccine provides protection against salmonellosis.…”
Section: Immunizationmentioning
confidence: 99%
“…CL studies are often conducted to investigate either serum or cellular defects in phagocytosis and microbicidal activity. Lowered CL values can be associated with reduced opsonic potential of the serum, or be reflective of the degree of MPO activity (Stjernholm et al 1973). The measured CL response is very low if cells deficient in MPO are stimulated (Rosen & Klebanoff 1976).…”
Section: Value Rankmentioning
confidence: 99%
“…Luminol enhanced CL by increasing the sensitivity of the technique reduces the number of cells required and has allowed investigation of neonates and neutropenic patients (60,62) Chemiluminescence and polymorphonuclear leukocyte function Sinee its initial diseovery (48) the measuretnent of CL has not only been used to assess the phagoeytic function of PMN's but also has been used to measure the specific and non-specific opsonic activity of serum (60,(63)(64)(65)(66)(67)(68)(69). While it is established (64), that PMN's from patients with chronic granulotnatous disease, myeloperoxidase deficiency or neutropenia have CL defects, the behaviour of PMN's from patients with bacterial infections is of some interest. Barbour et al (70) reported that peripheral blood PMN's of 18 patients during 19 episodes of active bacterial infection produeed increased CL when the produetion was compared to that of 29 uninfected controls.…”
Section: Luninol-enhanced Chemiluminescencementioning
confidence: 99%